Cranial fat dissemination following fat grafting for lumbar dural tear: First case report in the literature. (April 2021) - Alhendawy, Ibrahem; Tan, Darius; Homapour, Bob
Highlights: Direct fat grafting on sizable non-suturable dural tear should be avoided. Cranial fat dissemination can follow fat grafting for large non-suturable dural tear. Aseptic meningitis and hydrocephalus may result from cranial fat dissemination. Abstract: Introduction and importance: Dural tear and cerebrospinal fluid (CSF) leak is among the most common complications in lumbar spine surgery. Although primary dural suturing is the preferred method for repair, this is not always achievable specially with ventrolateral tears. Autologous fat grafting is one of the oldest and effective methods for dural repair which can also be used along with other methods of repair. This case report highlights a unique post spinal surgery complication with comment on how to avoid it. To our knowledge, this has not been previously reported in the literature. Case presentation: The authors report a sixty-seven-year-old male with lumbar pseudomeningocele and cranial fat dissemination following fat grafting for non suturable lumbar dural tear. This was demonstrated on magnetic resonance imaging (MRI) after her presented with low-pressure headache. Clinical discussion: Intraoperative dural tear is one of the most common complications in spinal surgery. Methods for optimal dural repair including fat grafting have been described but the choice still heavily dependent on the surgeon's preference and experience. Fat graft can migrate leading to potential undesirable further complications like hydrocephalus and aseptic meningitis. Conclusion: Cranial fat dissemination following fat grafting for lumbar dural tear should be recognized as a post-operative complication in lumbar spine surgery. It should be considered in case of hydrocephalus or aseptic meningitis post dural fat grafting. Surgeons should utilize adjunct methods to minimize its incidence.